Pengembangan E-Modul Menulis Karya Ilmiah Berbantuan Aplikasi Flipbook pada Siswa Kelas XI di SMA Negeri 10 Palembang - Aurelia, Olga; Nurhayati Nurhayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The research on the development of E-Modules conducted in class XI of SMA Negeri 10 Palembang aims to (1) Describe the results of the analysis of teacher and student needs for the development of e-modules for writing scientific papers assisted by flipbook applications, (2) Present the results of the development of e-modules for writing scientific paper assisted by applications, (3) Describe the results of the alpha test of the development of e-modules for writing scientific papers assisted by flipbook applications. The research and development methods used in this study are Alessi & Trollip. The steps are: (1) Planning stage (planning) by identifying needs analysis. (2) Design stage (design) by collecting designs and preparing prototypes. (3) Development stage (development) by developing the initial product or creating a product design, alpha test (expert validation), and revision. Data collection techniques were carried out using questionnaires, interviews, and expert validation. The alpha test (expert validation) was carried out by three experts, namely media, material experts, and language experts. The results of the media validation test showed a figure of 90% (very valid), material validation showed a figure of 85.4% (very valid), language validation showed a figure of 80% (valid). Based on the results of the validation test by three experts on the learning media assisted by the flipbook application for the material on writing scientific papers, it was declared valid or feasible to be used in class XI at SMA Negeri 10 Palembang.